Cholesterol glucosylation–based survival strategy in Helicobacter pylori. Issue 2 (23rd December 2020) - Qaria, Majjid A.; Qumar, Shamsul; Sepe, Ludovico P.; Ahmed, Niyaz
Abstract: Helicobacter pylori is a major chronic health problem, infecting more than half of the population worldwide. H. pylori infection is linked with various clinical complications ranging from gastritis to gastric cancer. The resolution of gastritis and peptic ulcer appears to be linked with the eradication of H. pylori . However, resistance to antibiotics and eradication failure rates are reaching alarmingly high levels. This calls for urgent action in finding alternate methods for H. pylori eradication. Here, we discuss the recently identified mechanism of H. pylori known as cholesterol glucosylation, mediated by the enzyme cholesterol‐α‐glucosyltransferase, encoded by the gene cgt . Cholesterol glucosylation serves several functions that include promoting immune evasion, enhancing antibiotic resistance, maintaining the native helical morphology, and supporting functions of prominent virulence factors such as CagA and VacA. Consequently, strategies aiming at inhibition of the cholesterol glucosylation process have the potential to attenuate the potency of H. pylori infection and abrogate H. pylori immune evasion capabilities. Knockout of H. pylori cgt results in unsuccessful colonization and elimination by the host immune responses. Moreover, blocking cholesterol glucosylation can reverse antibiotic susceptibility in H. pylori . In this work, we review the main roles of cholesterol glucosylation in H. pylori  and evaluate whether this mechanism can be targeted for the development of alternate methods for eradication of H. pylori infection.